PENGARUH DEBT TO EQUITY RATIO, RETURN ON ASSETS DAN RETURN ON EQUITY TERHADAP DIVIDEND PAYOUT RATIO (Studi Empiris Pada Perusahaan Real-Estate yang Listing di Bursa Efek Indonesia periode 2013-2015) - Ahson Nugroho; Budi Wahono; Muhammad Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
AbstractThe purpose of this research are : 1). Effeck of Debt To Equity Ratio to Divident PayoutRatio. 2). Influence of Return On Assets to Divident Payout Ratio. 3). Influence of Return OnEquity to Dividend Payout Ratio.The sample in this study is the financial statements of real estate companies listing onthe indonesian stock exchanges obtained from debt to equity ratio, Return On Assets andReturn On Equity and Dividend Payout Ratio in 2013-2015, the data source used insecondary data obtained of records or annual financial statements that have been recordedand recorded on the stock exchange of Indonesian. This research uses quantitative approach.The results showed that the Debt To Equity Ratio partially has a significant influence onDividend Payout Ratio, Return On Assets partially has a significant influence on DividentPayout Ratio and Retun On Equity partially has a significant influence on Dividend PayoutRatio.Key Words: Debt To Equity Ratio, Return On Assets, Return On Equity, Dividend payoutRatio